2018
DOI: 10.1016/j.cobme.2018.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Oral non-viral gene delivery for applications in DNA vaccination and gene therapy

Abstract: Non-viral gene delivery via the oral route is a promising strategy for improving outcomes of DNA vaccination and gene therapy applications. Unlike traditional parenteral administration routes, the oral route is a non-invasive approach that lends itself to high patient compliance and ease of dosing. Moreover, oral administration allows for both local and systemic production of therapeutic genes or, in the case of DNA vaccination, mucosal and systemic immunity. However, the oral route presents distinct challenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…In the case of anionic MPs, their surfaces have been functionalized with thiol functional groups to exhibit mucoadhesive properties by forming disulfide bonds with thiol groups existing in mucins [102,103,104,105,106,107]. Several studies have confirmed that such chemically-modified MPs show a significantly longer residence time in the target, acting as potential candidates for the sustained oral delivery of specific drugs, such as insulin and losartan [96,108].…”
Section: Challenges Associated With Oral Deliverymentioning
confidence: 99%
“…In the case of anionic MPs, their surfaces have been functionalized with thiol functional groups to exhibit mucoadhesive properties by forming disulfide bonds with thiol groups existing in mucins [102,103,104,105,106,107]. Several studies have confirmed that such chemically-modified MPs show a significantly longer residence time in the target, acting as potential candidates for the sustained oral delivery of specific drugs, such as insulin and losartan [96,108].…”
Section: Challenges Associated With Oral Deliverymentioning
confidence: 99%
“…In the biomedical genetics community, the greater emphasis on eliminating the causative factors underlying a disease rather than treating symptoms has led to the rapid development of approaches to gene therapy and gene delivery. Oral gene delivery has the potential to treat diseases specific to the gastrointestinal tract (GIT) such as ulcerative colitis and cancer and may also have broader therapeutic effects for diseases such as Type 2 diabetes [ 4 ]…”
Section: Introductionmentioning
confidence: 99%
“…Even if their ability to deliver genes is maintained, additional modifications are needed to achieve tissue specificity. 9,10 Among various cationic polymers, PEI has been widely used as a benchmark polymeric vector. 11,12 PEI condenses DNA to nanosized complexes (polyplexes) to facilitate endocytosis.…”
Section: Introductionmentioning
confidence: 99%
“…Although these materials are effective delivery agents in in vitro experiments, they are often ineffective when used in vivo. Even if their ability to deliver genes is maintained, additional modifications are needed to achieve tissue specificity. , …”
Section: Introductionmentioning
confidence: 99%